Therapeutic drug monitoring: antiarrhythmic drugs - Campbell, T J (Blackwell Science Inc, 2001)
Antiarrhythmic agents are traditionally classified according to Vaughan Williams into four classes of action. Class I antiarrhythmic agents include most of the drugs traditionally thought of as antiarrhythmics, and have as a common action, blockade of the fast-inward sodium channel on myocardium. These agents have a very significant toxicity, and while they are being used less, therapeutic drug monitoring (TDM) does significantly increase the safety with which they can be administered. Class II agents are antisympathetic drugs, particularly the b-adrenoceptor blockers. These are generally safe agents which do not normally require TDM. Class III antiarrhythmic agents include sotalol and amiodarone. TDM can be useful in the case of amiodarone to monitor compliance and toxicity but is generally of little value for sotalol. Class IV antiarrhythmic drugs are the calcium channel blockers verapamil and diltiazem. These are normally monitored by haemodynamic effects, rather than using TDM. Other agents which do not fall neatly into the Vaughan Williams classification include digoxin and perhexiline. TDM is very useful for monitoring the administration (and particularly the safety) of both of these agents.